2016
DOI: 10.5858/arpa.2015-0102-rs
|View full text |Cite
|
Sign up to set email alerts
|

Primary Biliary Mixed Adenoneuroendocrine Carcinoma (MANEC): A Short Review

Abstract: Mixed adenoneuroendocrine carcinomas (MANECs) are composite neoplasms with areas of adenocarcinoma or squamous cell carcinoma intermingled with neuroendocrine carcinoma or neuroendocrine tumor, each composing at least 30% of the neoplasm. MANECs are very infrequent overall, and they are more commonly diagnosed in the appendix, colon, and stomach. Biliary MANECs are particularly rare, and their histogenesis is debated because neuroendocrine cells are seldom identified in the normal biliary tract. They can show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…In 20 cases of colorectal AC with high-grade poorly-differentiated cell clusters, Gurzu et al reported that all AC expressed synaptophysin, but were negative for chromogranin (12). Further supporting this hypothesis, CD133 expression, a marker of cancer stem cells, has been found in varying amounts within different GI malignancies; including NET, NEC, AC, and in mixed adenoneuroendocrine carcinoma (MANEC) (13). MANEC tumors, recently characterized by the WHO in 2010, are composite neoplasms containing areas of adenocarcinoma or squamous cell carcinoma integrated with NEC or NET (with each component forming at least 30% of the neoplasm).…”
Section: Discussion Discussionmentioning
confidence: 93%
“…In 20 cases of colorectal AC with high-grade poorly-differentiated cell clusters, Gurzu et al reported that all AC expressed synaptophysin, but were negative for chromogranin (12). Further supporting this hypothesis, CD133 expression, a marker of cancer stem cells, has been found in varying amounts within different GI malignancies; including NET, NEC, AC, and in mixed adenoneuroendocrine carcinoma (MANEC) (13). MANEC tumors, recently characterized by the WHO in 2010, are composite neoplasms containing areas of adenocarcinoma or squamous cell carcinoma integrated with NEC or NET (with each component forming at least 30% of the neoplasm).…”
Section: Discussion Discussionmentioning
confidence: 93%
“…Sin embargo, para pacientes que no puedan tolerar la escisión radical, la escisión local puede ser una opción válida. Posterior a esto se debe adoptar un tratamiento multimodal con radioterapia adyuvante y/o quimioterapia 7,8 .…”
Section: Discussionunclassified
“…Mixed adenoneuroendocrine carcinoma (MANEC), has been described by WHO as a rare gastrointestinal neoplasm [1], histologically characterized by the presence of at least 30% each of epithelial and neuroendocrine components [2]. The tumor may appear in various levels of the digestive tract including the esophagus, stomach, colon and appendix [3][4][5][6][7], as well as other sites such as the pancreas [8], and urinary bladder [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor may appear in various levels of the digestive tract including the esophagus, stomach, colon and appendix [3][4][5][6][7], as well as other sites such as the pancreas [8], and urinary bladder [9][10][11][12]. Presence of MANEC in the gallbladder is exceedingly rare [2,[13][14][15]. Biological behaviour of MANEC seems to be quite unpredictable and the prognosis uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation